Querying Encrypted Data (Tutorial) - Arasu, Arvind; Eguro, Ken; Kaushik, Raghav; Ramamurthy, Ravi (29th International Conference on Data Engineering (ICDE), 2013)
Data security is a serious concern when we migrate data to a cloud DBMS. Database encryption, where sensitive columns are encrypted before they are stored in the cloud, has been proposed as a mechanism to address such data security concerns. The intuitive expectation is that an adversary cannot “learn” anything about the encrypted columns, since she does not have access to the encryption key. However, query processing becomes a challenge since it needs to “look inside” the data. This tutorial explores the space of designs studied in prior work on processing queries over encrypted data. We cover approaches based on both classic client-server and involving the use of a trusted hardware module where data can be securely decrypted. We discuss the security challenges that arise in both approaches and how they may be addressed. Briefly, supporting the full complexity of a modern DBMS including complex queries, transactions and stored procedures leads to significant challenges that we survey.
Tutorial presentation